Group Threat, Racial/Ethnic Animus, and Punitiveness in Latin America: A Multilevel Analysis. (October 2022) - Lehmann, Peter S.; Chouhy, Cecilia; Singer, Alexa J.; Stevens, Jessica N.; Gertz, Marc
The group threat perspective has been tested with regard to a variety of social control outcomes, including public support for punitive crime control policies. However, little work has explored possible interactive effects between macro-level racial/ethnic contexts, individual-level racial/ethnic animus, and race/ethnicity on punitive attitudes, and none of this research has been conducted outside the United States. The current study is the first to examine these interrelationships in Latin America, which is characterized by notable racial/ethnic stratification and recent movements toward authoritarian criminal justice strategies. Analyses of data from the AmericasBarometer survey collected in 633 municipalities within 10 countries ( N = 16, 782) reveal that (1) racial/ethnic animus is consistently predictive of support for harsher punishments, (2) the effect of being White on punitiveness is conditioned by Indigenous population size at the municipal level, and (3) the interactive effects of being White and holding anti-Black animus are further moderated by municipal-level percent Black/Mulatto.